Network simulation experiments manual - Aboelela, Emad (Morgan Kaufmann, 2003)
The lab exercises contained in the network simulation experiments manual are based on the OPNET simulator (v. 9), a network simulation tool that was originally developed at M.I.T. It provides networking professionals with the option of implementing experiments from their homes or workplaces and the lab manual comes with directions for downloading the free easy-to-install software (special version to this book only--see system requirements below). These labs run through simulations closely tied to the material in the text so that you can visualize the discussions covering core network topologies. Various scenarios are presented within each topology, and review questions and a lab report exercise accompany each lab experiment. The experiments also follows the organization of Computer Networks, Third Edition, by Larry Peterson and Bruce Davie.